Game for Sasak Script Based on Knuth Morris Pratt Algorithm and ADDIE Model - Muhammad Tajuddin; Ahmat Adil; Andi Sofyan Anas (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2022)
Knowledge of the Sasak script is very few Sasak people are interested in learning it. The writing system of the Sasak script is in danger of becoming extinct, so the local government must carry out literacy education so that the Sasak script does not become extinct from the face of the Lombok earth and must be applied to elementary and junior high schools, not only in the learning and teaching process. Directing children can be done by introducing them to the game-based Sasak baluk olas script. The Sasak script game based on KMP (Knuth Morris Pratt) Algorithm and ADDIE (Analysis, Design, Development, Implementation, Evaluation) which integrates game thinking and game elements has proven helpful in learning new knowledge. For this reason, the purpose of this study is to discuss how to develop applications for the Sasak Baluk Olas script on smartphones based on the Android system. designed based on the famous visual novel concept that combines multimedia elements including audio, animation, graphics, and images to make it more interesting and lively. All of these elements combine with gamification elements such as quizzes, rewards, badges, and feedback to make it a gamification application. Based on all the abilities of the Sasak Baluq Olas script, it can help potential users, especially elementary and junior high school students in Mataram City to increase the level of understanding and awareness of the Sasak script so that it does not become extinct